Pseudomonas aeruginosa at the dawn of a post-antibiotic era: clinical significance, resistance mechanisms, novel antibiotics and alternative treatments - Orsolya KOVÁCS; Endre JAKAB (Studia Universitatis Babeș-Bolyai. Biologia, 2020)
Since their discovery, antibiotics have helped treat diseases prior to which many were untreatable, saving millions of lives. However, due to the overuse of antibiotics in medicine and agriculture, the advent of resistant strains of bacteria followed shortly after. The current antibiotic resistance crisis is bringing humanity closer to a post-antibiotic era, when all the advancements made by modern medicine could easily be reversed. Pseudomonas aeruginosa is a Gram-negative, rod-shaped bacterium, ubiquitous owing to its minimal nutritional and growth requirements. P. aeruginosa is one of the pathogens included in the priority list of the WHO, being assessed as critical due to its high antimicrobial resistance, leaving only a few effective treatment options to combat it. As an opportunistic pathogen, P. aeruginosa establishes infection in immunocompromised patients, primarily in hospital settings. In order to initiate infection, it requires several virulence factors that mediate the invasion of the pathogen into host cells. Owing to the multiple resistance mechanisms of P. aeruginosa, it has developed resistance to most classes of antibiotics. Due to its increased resistance, treating P. aeruginosa infections is a great challenge for clinicians. Several β-lactam/β-lactamase combinations have been approved and are available as treatment options, which overall show high efficacy against P. aeruginosa. Moreover, novel antibiotics are currently in development as possible antipseudomonal agents, including a Pseudomonas-specific formulation. In addition, new strategies such as bacteriophage therapy, pyocins or the inhibition of the quorum sensing system are being investigated for the treatment of P. aeruginosa infections.